Open-source modelling infrastructure: Building decarbonization capacity in Canada. (November 2022) - McPherson, Madeleine; Monroe, Jacob; Jurasz, Jakub; Rowe, Andrew; Hendriks, Richard; Stanislaw, Lauren; Awais, Muhammad; Seatle, Madeleine; Xu, Robert; Crownshaw, Timothy; Miri, Mohammad; Aldana, Dustin; et al.
Abstract: Actions that transform our energy system are the cornerstone of decarbonizing our economy but have been hindered by the ineffective interface between researchers and decision-makers in Canada. This paper begins by arguing for a more holistic perspective on energy system decarbonization modelling and exploring how insights can aid evidence-based decision making. We then respond with the development of a modelling platform that includes three core pillars: (1) a toolbox of models that together represent the integrated energy system, (2) a dataset containing the inputs required to populate those models, and (3) a visualization suite to analyze and communicate their outputs. The Spine Toolbox is leveraged to process these three components in an efficient workflow. Taken together, the platform promotes the usability of model results by fostering consistency, transparency, and timeliness. Furthermore, the epistemic limitations of energy systems modelling and implications for platform and model design, and engaging extended peer communities, are discussed. Our hope is that this platform can be a foundational resource that facilitates collaboration between energy system and decarbonization researchers, modelling teams and decision-makers, ultimately enabling the effective application of evidence-based policy. Highlights: Argues that energy systems integration is a key element of system decarbonization modelling. Reviews the current landscape of energy systems models and priorities in Canada. Presents an open-source toolkit for modelling Canada's energy system and its decarbonization. Describes how the toolkit can facilitate evidence-based decision making. Refer to MethodsX for user manuals: SILVER model, COPPER manual, CODERs database, IDEA suite.